Disruption of estrogen receptor beta’s DNA binding domain impairs its tumor suppressive effects in triple negative breast cancer - Aspros, Kirsten G. M.; Emch, Michael J.; Wang, Xiyin; Subramaniam, Malayannan; Hinkle, Megan L.; Rodman, Esther P. B.; Goetz, Matthew P.; Hawse, John R. (Frontiers in Medicine, 2023)
Triple negative breast cancer (TNBC) is an aggressive sub-type of the disease which accounts for a disproportionately high percentage of breast cancer morbidities and mortalities. For these reasons, a better understanding of TNBC biology is required and the development of novel therapeutic approaches are critically needed. Estrogen receptor beta (ERβ) is a reported tumor suppressor that is expressed in approximately 20% of primary TNBC tumors, where it is associated with favorable prognostic features and patient outcomes. Previous studies have shown that ERβ mediates the assembly of co-repressor complexes on DNA to inhibit the expression of multiple growth promoting genes and to suppress the ability of oncogenic transcription factors to drive cancer progression. To further elucidate the molecular mechanisms by which ERβ elicits its anti-cancer effects, we developed MDA-MB-231 cells that inducibly express a mutant form of ERβ incapable of directly binding DNA. We demonstrate that disruption of ERβ’s direct interaction with DNA abolishes its ability to regulate the expression of well characterized immediate response genes and renders it unable to suppress TNBC cell proliferation. Loss of DNA binding also diminishes the ability of ERβ to suppress oncogenic NFκB signaling even though it still physically associates with NFκB and other critical co-factors. These findings enhance our understanding of how ERβ functions in this disease and provide a model system that can be utilized to further investigate the mechanistic processes by which ERβ elicits its anti-cancer effects.